A redox conducting polymer of a meso-Ni(II)-SaldMe monomer and its application for a multi-composite supercapacitor. (1st April 2018) - Łępicka, Kamila; Pieta, Piotr; Gupta, Ruma; Dabrowski, Marcin; Kutner, Wlodzimierz
Abstract: A film of a new redox conducting polymer, named poly[ meso -Ni(II)-SaldMe], was prepared by electropolymerization of a meso - N, N ′-bis-(salicylidene)-2, 3-butanediaminonickel(II)] monomer, meso -Ni(II)-SaldMe. The poly[ meso -Ni(II)-SaldMe] film revealed electroactivity in the potential range of 0.30–1.10 V vs. Ag/Ag + and high durability. Specific capacitance, SC, of the film was ∼210 F g −1 (37.2 mF cm −2 ) at the scan rate of 5 mV s −1 . The poly( meso -Ni(II)-SaldMe) film was utilized to fabricate a laboratory model of a new asymmetric supercapacitor with a dual anode and a dual cathode. Composites of reduced graphene oxide, RGO, with polypyrrole (PPy) and poly[ meso -Ni(II)-SaldMe] served as a positive electrode (dual anode) while the negative electrode (dual cathode) consisted of composites of RGO with a C60 -based polymer and PPy. The fabricated device exhibited a very broad working voltage range of 0–2.20 V in the 0.1 M (TBA)PF6 solution of propylene carbonate, thus allowing for maximum charging of all composite electrodes and delivering a high energy density of 102.60 W h kg −1 (18.2 μW h cm −2 ) at the power density of 12.21 kW kg −1 (2.2 μW cm −2 ). The life-time of charge-discharge cycling of this supercapacitor was excellent retaining 91% of its SC after 10 000 consecutive cycles. Graphical abstract: